Effect of enzyme treatment on nutritive value of palm kernel expeller cake. - Saenphoom, P.; Liang, Juan Boo; Ho, Yin Wan; Loh, Tech Chwen; Mohamad, Rosfarizan (2011)
The objective of this study was to examine the effects of enzyme treatment on nutritive value of palm kernel expeller (PKE). The experiment consisted of 2 treatments; PKE with or without enzyme incubated in 80% water at 65% for 18 hours. Enzyme treatment significantly reduced (P<0.01) NDF and ADF contents. Similarly the gross energy of enzyme treated PKE was higher than the control (P<0.01). The results suggested that the tested enzyme worked efficiently to break down hemicelluloses mannans in PKE.